1995
DOI: 10.1007/bf01691492
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis in HIV-infected patients

Abstract: To determine the prevalence and the clinical and serological findings of neurosyphilis in HIV-infected patients, Treponema pallidum hemagglutination (TPHA) tests, CD4+ lymphocyte counts and determination of rapid plasma reagin (RPR) titers were performed in 972 HIV-infected patients over a period of 3.5 years. Patients were scored according to the Centers for Disease Control's classification for HIV infection. Reactive serum syphilis tests and positive cerebrospinal fluid (CSF)-Venereal Disease Research Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 16 publications
1
21
0
8
Order By: Relevance
“…Treatment of syphilis in HIV positive people can be an important means of preventing HIV transmission. The incidence of syphilis among HIV-positive individuals is difficult to estimate, but seroprevalence studies have shown evidence of previous exposure to Treponema pallidum in 3% to 35% of HIV-positive patients 3,4,12) . Concurrent HIV infection may alter the progression of syphilis by increasing the propensity of the disease to progress to neurosyphilis, decreasing the latency period before the onset of neurosyphilis, increasing the severity of the manifestations of neurosyphilis, or rendering standard therapy for primary and secondary syphilis inadequate 13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of syphilis in HIV positive people can be an important means of preventing HIV transmission. The incidence of syphilis among HIV-positive individuals is difficult to estimate, but seroprevalence studies have shown evidence of previous exposure to Treponema pallidum in 3% to 35% of HIV-positive patients 3,4,12) . Concurrent HIV infection may alter the progression of syphilis by increasing the propensity of the disease to progress to neurosyphilis, decreasing the latency period before the onset of neurosyphilis, increasing the severity of the manifestations of neurosyphilis, or rendering standard therapy for primary and secondary syphilis inadequate 13) .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of neurosyphilis in the HIV-positive population is probably 3-35% 3) . The number of acquired immune deficiency syndrome (AIDS) patients is on the increase even in Korea, therefore the number of patients with neurosyphilis is also expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…En los pacientes con VIH, la afección del SNC es más frecuente que en la población sin el VIH 5 . Así, en un estudio español 37 , la prevalencia de neurolúes por determinación del test de serología luética (VDRL, venereal disease research laboratory) en el líquido cefalorraquídeo (LCR) en pacientes VIH con sífilis no tratada fue del 23,5%, y la mayoría de los pacientes presentaba cefalea moderada. Aunque la afección del SNC en los individuos con VIH es con más frecuencia asintomática, la clínica puede ser muy diversa, y puede incluir cefalea, alopecia, meningomielitis, síndromes medulares, goma con manifestaciones focales, alteraciones del comportamiento y deterioro cognitivo 5,37,38 .…”
Section: Clínicaunclassified
“…Así, en un estudio español 37 , la prevalencia de neurolúes por determinación del test de serología luética (VDRL, venereal disease research laboratory) en el líquido cefalorraquídeo (LCR) en pacientes VIH con sífilis no tratada fue del 23,5%, y la mayoría de los pacientes presentaba cefalea moderada. Aunque la afección del SNC en los individuos con VIH es con más frecuencia asintomática, la clínica puede ser muy diversa, y puede incluir cefalea, alopecia, meningomielitis, síndromes medulares, goma con manifestaciones focales, alteraciones del comportamiento y deterioro cognitivo 5,37,38 . Se ha indicado también que el VIH acelera y modifica el curso clínico de la neurolúes y que las complicaciones neurológicas son más frecuentes y pueden aparecer con cualquier grado de inmunodepresión 5,39 .…”
Section: Clínicaunclassified
“…Its pathogenesis remains unclear, and it was thought to be a disease of the past. However, the spread of HIV infection has led neurosyphilis to becomea problem again, because co-infection with HIVleads syphilis to showan atypical and rapid clinical course, with resistance to the previously recommended treatment (1)(2)(3). Selective IgA deficiency is also uncommon,and its pathogenesis and clinical importance are not well understood.…”
Section: Introductionmentioning
confidence: 99%